Comprehensive Electrocardiology - Macfarlane, Peter W.; van Oosterom, A.; Pahlm, Olle.; Kligfield, Paul.; Janse, Michiel; Camm, John.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
New edition of the classic complete reference book for cardiologists and trainee cardiologists on the theory and practice of electrocardiography, one of the key modalities used for evaluating cardiology patients and deciding on appropriate management strategies.
Keywords: Medicine; Human physiology; Cardiology; Medicine & Public Health; Cardiology; Human Physiology